Perbedaan Luaran Klinis Jangka Panjang Komisurotomi Mitral Transvena Perkutan Berdasarkan Kriteria Keberhasilan Ekokardiografi Dan Kateterisasi - Diah R Widowati; Yoga Yuniadi; Nani Hersunarti (The Indonesian Heart Association, 2010)
Background. Balloon Mitral Valvuloplasty (BMV) can provides effectively the mechanical obstruction relief in mitral stenosis. Achieving a successful BMV based on echocardiographic criteria potentially increase mitral regur-gitation complication. In addition, long-term clinical outcome of a successful BMV based on catheterization criteria has not been widely elaborated. This study aims to compare the long-term clinical outcome of BMV based on the echocardiographic criteria and the catheterization criteria. Methods. A cross sectional study was conducted in mitral stenosis patients after BMV procedure. Patients was divided into 2 groups based on suc-cessful echocardiographic criteria (MVA = 1,5 cm 2vs MVA < 1,5 cm2). The long-term clinical outcome was evaluated using 6 minute walk test and SF-36 questionnaire. Results. Twenty two female patients were fulfilling study criteria with aged 38,8 ±12,0 years and 63,6% in atrial fibrillation. The characteristic between two groups were not significantly different. Six minute walk test results was not significantly different between two groups (6,6 ±0,8 vs 7,3±1,0 p = 0,103). SF-36 physical components summary was not significantly different between two groups (43,0±7,5% vs 42,1±6,7 p = 0,770). Also, SF-36 mental components summary was not significantly different between two groups (50,7±5,9 vs 53,9±8,9 p = 0,338).Conclusion. There was no significantly different of long-term clinical out-come between the echocardiographic criteria of successful BMV and the catheterization criteria of successful BMV.